Graft polymerization of flame-retardant compound onto silk via plasma jet - Chaiwong C. (2017)
We investigated the application of an atmospheric pressure plasma jet to impart flame retardancy to silk fabrics. Argon plasma jet was used to graft non-durable phosphorus-based flame retardant agent (Pyrovatim® PBS) onto silk. The treated fabric showed a higher level of flame retardancy as evaluated by using 45° flammability test. To evaluate the durability, the treated silk was submitted to washing process. It was found that Ar plasma conferred durable flame retardancy to the treated silk fabric since the flame retardant character retained after the washing process. Scanning electron microscopy revealed that the yarn of the Ar treated silk was uniformly covered with the PBS particles whereas PBS deposited locally on the untreated silk. Energy dispersive X-ray spectroscopy showed the presence of phosphorus up to 11. wt.% in the Ar treated silk. Fourier transform infrared spectroscopy exhibited the bondings between phosphorus and the silk molecular chains. The molecular dynamics simulations affirmed the incorporation of phosphorus in the structure of silk. © 2010 Elsevier B.V.